Development of Information Technology-Based Community Health Promotion Applications to Improve Public Health - Musaidah Musaidah; Rosdiana Rosdiana; Arriani Indrastuti; Lumastari Ajeng Wijayanti (Asosiasi Guru dan Dosen Seluruh Indonesia, 2026)
The development of information technology offers significant opportunities to increase the effectiveness of health promotion in the community. The use of information technology-based applications can provide easily accessible, interactive, and sustainable health education media. This study aims to develop and evaluate an information technology-based community health promotion application to improve public health knowledge and behavior. This study used a research methodology. and This research was conducted in the field of health promotion development (R&D) with a quantitative approach. The research sample was the community in the X community area. Data were collected through questionnaires before and after using the application, then analyzed descriptively and inferentially. The results of the study showed an increase in public health knowledge and behavior after using the health promotion application. The conclusion of this study is that the information technology-based health promotion application is effective as a community health promotion medium.